Centers for Teaching and Learning : The New Landscape in Higher Education - Wright, Mary C., 1971- (Book collections on Project MUSE., 2023)
"Universities are refocusing on pedagogy--how we teach and learn what we know--and they have placed that work in new centers for teaching and learning (CTL). In this book, the author maps the landscape of 1,200+ US centers and programs --including medical and professional school programs-- through another approach: coding of their websites. This data allows insight into CTL strategy and operations, and it offers a picture of a fuller near-population of centers (rather than a small sample of center directors)"--